The distribution and relationship between 3D LVEF and 3D strain in a general population. (25th November 2020) - Ericsson, F; Tayal, B; Zaremba, T; Schnohr, P; Jensen, G; Mogelvang, R; Soegaard, P
Abstract: Introduction: Three-dimensional (3D) echocardiography (3DE) is currently extensively used to estimate left ventricle (LV) morphology and heart valves. However, it is underutilized in the assessment of LV function. Most likely, it is due to limited knowledge of the normal reference intervals. In order to fill this knowledge gap, studies which investigates the 3DE reference ranges in a larger cohort of a general population are needed. The objective of the current study was to study the relationship and distribution of 3D LV ejection fraction (EF) and its corresponding strain values in subjects enrolled in Copenhagen City Heart Study (CCHS). Methods: The echocardiograms were acquired from CCHS subjects from 2011–2014 by using GE Vivid E9 (GE Medical, Copenhagen, Denmark), during four consecutive heart beats. Exclusion critera were missing data or measurements in 3D, poor image quality or frame rate (<12 fps) and, based on visual evaluation of the echocardiograms, inappropriate tracking of three or more myocardial segments in the strain analysis. The echocardiograms were analysed in 2019 on EchoPacTM v. 201 (GE Medical, Copenhagen, Denmark). Results are presented in means, interquartile ranges (IQR) and as adjusted correlation values (r 2 ). R 2 values equal to or above 0.64 (equals to r=0.8) were considered as strong correlation. LV function parameters included were LVEF, global longitudinal strain (GLS), global circumferential strain (GCS) and area strain (AS). LVEF and strain results are presented as percentages (%). The distribution and relationship between 3D LVEF, GLS, GCS and AS are visualized as scatter plots and box-whiskers plots. The statistical analysis and the visualisation of the data was performed in RStudio v. 3.5.1. P-values <0.005 were considered as markers for statistical significance. Results: There were 2955 subject with available 3DEs in CCHS among which 1202 subjects had sufficient image quality for evaluation. The mean 3D LVEF was 54.6% (IQR: 50–60%), 3D GLS −14.5% (IQR: −13 to −16), 3D GCS −13.4% (IQR: −11 to −15) and AS −24.7% (IQR: −22 to −27). The adjusted correlation values between LVEF with strain parameters were: 0.04 (GLS), 0.37 (GCS) and 0.26 (AS), which was poor. Conclusion: This study provides valuable data of the distribution of 3D LVEF and its corresponding 3D strain values in a general population. The 3D strain values are lower than the reference interval described in literature for two-dimensional echocardiography. Moreover, correlation was also found to be poor between LVEF and different strain parameters. Funding Acknowledgement: Type of funding source: None